Land Suitability Assessment for Agriculture Using Analytical Hierarchy Process in Northern Parts of Khalkhal County (Case Study: Mikaeel Abad catchment) - Fatemeh Nazari Viand; Hossein Koohestani; Shapoor Zarifian; Fatemeh Kazemieh (Journal of Agricultural Science and Sustainable Production, 2020)
Continuous exploitation of renewable natural resources needs to identify the land ecological capability and this identification permit to exploit of the natural resources correctly by programed and optimum management. The purpose of this research is to land suitability assessment for agriculture activity using FUZZY-AHP method in Mikaeel abad catchment located in northern part of Khalkhal county, Ardabil. 13 factors including precipitation, Vegetation density, Vegetation production, slope, soil erosion, distance from water, vegetation type, soil hydrologic group, Geology, Soil depth, soil texture, soil penetrating and current land use utilized to land capability assessment in ArcGIS10 surrounding. To weigh the criteria AHP and to apply same scale to criteria Fuzzy method was used and using Weighted Linear Combination method all criteria were overlaid and potential map was prepared. Final potential map classified in 4 potential classes using natural break classification method. Classes with potential category from 1 to 2 (65% of area) were allocated to agriculture class and category from 3 to 4(35% of area) were allocated to non-agricultural activities. Also conformity map between current land use map and potential map showed that in 61.8% of area there is conformity between current land use map and potential categories map for agriculture activity. It is suggested that consideration be given to mapping of potential classes based on the ecological capability of the study area in assigning agricultural uses and activities. In this regard, it is advisable to carry out agricultural activities in areas with class I capacity in the form of irrigated farming or Gardening, And in areas with the capacity of the second potential class dry farming, and in the third and fourth potential class no agricultural activity will be carried out.